SAT0457 Efficacy and Safety of Etanercept in Combination with Methotrexate in the Patients with Early and Late Juvenile Idiopathic Arthritis. (23rd January 2014) - Alekseeva, E.; Bzarova, T.; Fetisova, A.; Valieva, S.; Isayeva, K.; Denisova, R.; Sleptsova, T.; Mitenko, E.; Chistyakova, E.
Abstract : Background: The use of biological products in the therapy of juvenile idiopathic arthritis (JIA) enables to achieve sustained remission of the disease and to improve the prognosis. Objectives: To assess efficacy and safety of Etanercept plus Methotrexate combination in the patients with early and late JIA. Methods: 97 children with various JIA variants were examined. The patients were stratified into 2 groups: with late arthritis, the disease duration > 2 years (Group 1, n=66), with early arthritis, the disease duration < 2 years (Group 2, n=31). Average age of the children in Group 1 was 9.5 (3;17.0) years, in Group 2 – 5.0 years (1.0;14.0) years. The patients received subcutaneous Etanercept twice a week at the dose 0.4 mg/kg on top of Methottrexate at 15 mg/m 2 /week. The observation period was 52 weeks. Therapeutic efficacy was assessed in accordance with American College of Rheumatology criteria (ACR Pedi) as 50, 70, 90% improvement and remission criteria (Wallace, 2011). Results: Based on ACR Pedi, one month after onset of Etanercept therapy 50% improvement was observed in 36% and 52% children in Groups 1 and 2, 70% improvement in 14% and 36% children, 90% improvement in 4% and 23% children, respectively. At 3 months 50%, 70%, 90% improvement was achieved in 51%, 44%, 50% of patients in Group 1 compared with 92%, 68% and 84% of patients in Group 2. At 6 months 50% improvement was recorded in 64% patients in Group 1 and in 96% patients in Group 2; 70% improvement – in 52% and 83% patients, respectively, 90% improvement was observed in 49% patients in Group 1 and у 78% patients in Group 2. Inactive disease stage was recorded in 71% patients in Group 1 and in 100% patients in Group 2. Twelve months after onset of treatment inactive disease stage was observed in 100% patients of the both groups; remission was observed in 71% patients in Group 1 and in 100% patients in group 2. In 11 patients Etanercept wsa discontinued for the following reasons: in 5 patients for inadequate efficacy; 1 patient for persistent local allergic reaction, in 3 patients for aggravation of JIA systemic manifestations; in 2 patients for development of rheumatoid uveitis. Adverse events were mild or moderate and included acute bronchitis, herpetic infection aggravation; acute rhinitis, and pain in administration site. Conclusions: High efficacy and safety of Etanercept in the patients with early and late JIA was demonstrated. In the patients with early JIA the time to effect development is significantly shorter. Disclosure of Interest: None Declared